Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
1)-5(x-3)= -5x+15
2) 3(5-x)= 15-3x
3) -5(3-x)= -15+5x
4)-3(-5+2x)+x=-5x+15
5)5(3-x)= 15-5x
Your answer would be 5) 5(3-x).
2) 3(5-x)= 15-3x
3) -5(3-x)= -15+5x
4)-3(-5+2x)+x=-5x+15
5)5(3-x)= 15-5x
Your answer would be 5) 5(3-x).
Answer:
-3(-5+2x)+x
Step-by-step explanation:
First you have to use Distributive Property and multiply -5 and 2x by -3. you should have -6x+15+x. then you have to combine like terms but subtract -6x and x which gives us 5. your answer should be -5x+15. You can rearrange the answer to be 15 - 5x.
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.